Effect of Micronutrients Soil Supplementation on Sugarcane in Different Production Environments: Cane Plant Cycle - Mellis, Estevao Vicari; Quaggio, Jose Antonio; Goncalves Becari, Gustavo Ricardo [UNESP]; Junqueira Teixeira, Luiz Antonio; Cantarella, Heitor; Ferreira Dias, Fabio Luiz (Amer Soc Agronomy, 2016)
Fertilization of sugarcane (Saccharum spp.) with micronutrients is not common and this can affect crop yield. Research results of micronutrients in sugarcane in Brazil are still scarce and inconclusive. The aim of the present study was to assess the sugarcane crop response to Cu, Zn, Mn, Mo, and B fertilization in different sugarcane production environments in the state of Sao Paulo, Brazil. An experiment was conducted at 11 locations. The treatments consisted of the application of fixed micronutrient doses only to the planting furrow as follows: control, Zn (10 kg ha(-1)), Mn (10 kg ha(-1)), Cu (10 kg ha(-1)), B (3 kg ha(-1)), Mo (2 kg ha(-1)), and complete (Zn + Mn + Cu + B + Mo). The design consisted of a randomized block with five replicates. The leaf content, tillering, sugarcane yield, and total recoverable sugar were determined in cane plant. The responses varied with location, soil type, climate, and variety. Positive responses to micronutrients application were observed in all parameters studied with the exception of total recoverable sugar. The sugarcane yield increased significantly with the application of micronutrients in the following order of magnitude: Zn > Mo = Mn > Cu > B = Complete, with yield gain of 18, 12, 12, 10, 9, and 9 tonnes of cane per hectare (TCH), respectively. Sugarcane responded positively to micronutrient, especially Zn fertilization, demonstrating that this practice may be economically viable and increase the productivity of Brazilian sugarcane fields, making agribusiness sugarcane more sustainable.